2016
DOI: 10.1002/asia.201600906
|View full text |Cite
|
Sign up to set email alerts
|

Improved Electrochromic Performance of Poly(3,4‐ethylenedioxythiophene) by Incorporating a Three‐Dimensionally Ordered Macroporous Structure

Abstract: In this paper, three-dimensionally ordered macroporous (3DOM) poly(3,4-ethylenedioxythiophene) (PEDOT) films were electropolymerized from an ionic liquid, 1-butyl-3-methylimidazolium hexafluorophosphate ([Bmim]PF ). The electrochromic performances of the 3DOM PEDOT films were studied. The 3DOM films exhibited high transmittance modulation (41.2 % at λ=580 nm), high ionic fast switching speeds (0.7 and 0.7 s for coloration and bleaching, respectively), and enhanced cycling stability relative to that exhibited b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Nyquist plots and the fitted lines of their films based on Randles type equivalent circuit model are shown in Figure . R2 represents the resistance of the electrochromic films. …”
Section: Resultsmentioning
confidence: 99%
“…Nyquist plots and the fitted lines of their films based on Randles type equivalent circuit model are shown in Figure . R2 represents the resistance of the electrochromic films. …”
Section: Resultsmentioning
confidence: 99%
“…For instance, Zhang reported three-dimensionally ordered macroporous (3DOM) PEDOT films, which exhibited an ultrafast ionic fast switching speeds, high transmittance modulation, and enhanced cycling stability. 16 Hu prepared natural tubular clay halloysite nanotube (HNT)@poly (3,4- high optical contrast and long cycle stability. 17 Combing PEDOT with another electrochromic materials to take advantage of the synergistic effect is another method.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the electrochromic process of conducting polymers is dominated by electrochemical reaction, which consists of electron transmission and ion intercalation. Typically, better optical performance can be considerably facilitated by increasing the specific surface areas, conductivity, and accessible intercalation sites. , As a result, various geometric and electrical structures of PEDOT films have been created to improve their electrochromic properties. For instance, Zhang reported three-dimensionally ordered macroporous (3DOM) PEDOT films, which exhibited an ultrafast ionic fast switching speeds, high transmittance modulation, and enhanced cycling stability . Hu prepared natural tubular clay halloysite nanotube (HNT)@poly­(3,4-ethylene­dioxy­thiophene) (PEDOT) nanocomposites with enlarged active surface area and shortened ion diffusion distance, delivering high optical contrast and long cycle stability .…”
Section: Introductionmentioning
confidence: 99%
“…Electrochromic (EC) conjugated polymers(CPs) have attracted more and more attention for their great potential application in smart windows, displays and switchable mirrors, [1][2][3] owing to their abundant structure modification, fast switching time, outstanding coloration efficiency and color adjustment [4][5][6][7] and so on. Recently, the cross-linked polymer network configuration based on a star-shaped monomer structure being of a central core and three peripheral arms is found to be attractive to more and more researchers for the design of electrochromic materials, [8][9][10][11][12] because of the possible microporous structure induced fast color switching speed [13][14][15] and the non-linear molecular structure enhanced electrochemical stability. 16,17 Besides, the whole polymeric conjugation degree based on star-shaped structural monomers may be effectively controlled by adjusting the conjugation degree of the peripheral arm groups due to the non-linear metaposition-like linkage at the central core which may break the conjugation between the adjacent peripheral arms.…”
Section: Introductionmentioning
confidence: 99%